Teacher Readiness, Belonging, and Cultural Awareness: A Model for International Teacher Induction - English, Thomas A (East Carolina University, 2021)
Attrition rates at international schools are often high, requiring annual rounds of new teacher hiring. Although many of the teachers possess prior experience, they require personal and professional supports to be ready for the new teaching assignments and to adjust to unfamiliar settings. In a qualitative study at the Thai-Chinese International School in Bangkok, Thailand, a Co-Practitioner Researcher (CPR) team designed a phased teacher induction program to address the orientation, support, and professional growth needs of new teachers and carried it out with two cohorts of recently hired teachers. Using improvement science principles and Community Learning Exchange (CLE) protocols over three iterative cycles of inquiry, the CPR team and the new teachers planned, facilitated, and reviewed data from CLEs, focus groups, observations, and design-thinking activities. The induction process was expanded from a 1-week orientation to an extensive teacher induction program that lasted from the time of hire through the entire first year of employment. Thai and Chinese instructors and directors were more equitably involved in the induction process, which previously had been dominated by Western faculty and staff. The incoming cohort of teachers experienced improved readiness, feelings of welcome and belonging, and enhanced cultural awareness of the school and its host country. Other international schools that engage new teachers through a structured teacher induction program may obtain similar results, especially if they employ a participatory design process when establishing their induction practices.
Keywords: induction; orientation; cultural awareness; International schools--Thailand; Mentoring in education--Thailand; First year teachers--Thailand--Cross-cultural studies